How to quantify thermal acclimation capacity?. (24th March 2019) - Einum, Sigurd; Ratikainen, Irja; Wright, Jonathan; Pélabon, Christophe; Bech, Claus; Jutfelt, Fredrik; Stawski, Clare; Burton, Tim
Abstract : The capacity of organisms to acclimate will influence their ability to cope with ongoing global changes in thermal regimes. Here we highlight methodological issues associated with recent attempts to quantify variation in acclimation capacity among taxa and environments, and describe how these may introduce bias to conclusions. We then propose a measure of thermal acclimation capacity that more directly quantifies the process of acclimation. Future studies of variation in acclimation capacity should critically evaluate whether their chosen empirical metric accurately reflects the theoretical concept of acclimation.